Pattern of self-medication amongst housewives vs working women in urban population in Southern Rajasthan - Atray, Meena; Vijay, Radhika (International Journal of Basic & Clinical Pharmacology, 2018)
Background: The use of medications without prior medical consultation regarding indication, dosage, and duration of treatment is referred to as self-medication1. Self-medication has its own benefits regarding reduction in load and cost of medical services. Women are primarily responsible for the health needs of the family and self- medication is frequently practiced by them. Working environment may influence the attitude of women towards safe and rational self-medication. This study focuses on the pattern and attitude of women (housewives/ working) towards self- medication and influence of working atmosphere and exposure of women on self-medication. Methods: 170 women of age group 18-60 years were included in the study and after taking permission from Institutional ethics committee. Data was collected by making the participants fill a semi structured detailed questionnaire under observation of instructor. The data was analysed using Microsoft excel and compared by using Fischer exact test. Results: Most common ailment for which self-medication was practiced was pain. Working women primarily used pharmacist and house wives use old experience and family friends as primary source of information. Working women were more cautious about adverse drug reactions, drug-drug interactions, expiry date of medicine, reading instruction manual, use of counterfeit medicine and referring the experience to their known subjects as compare to housewives. Conclusions: Self-medication was prevalent in both the groups, though working environment has positive influence towards safe, responsible and rational self-medication. There is need for education regrading safe use of medicine and strict rules and regulations for availability of drugs.